Respostas
respondido por:
1
Temos as equações:
3x-2y=3
4x=12
Temos o valor de x em:
4x=12
x=12/4
x=3
Temos o valor de y em:
3x-2y=3
3(3)-2y=3
-2y=-6
y=-6/-2 = 6/2 = 3
3x-2y=3
4x=12
Temos o valor de x em:
4x=12
x=12/4
x=3
Temos o valor de y em:
3x-2y=3
3(3)-2y=3
-2y=-6
y=-6/-2 = 6/2 = 3
lindagata2:
3x-2y=3
respondido por:
0
3x-2y=3 e 4x=12
x=12/4 tirar prova a limpo: 3x -2y=3 3(3)-2(3)=3
9-6=3
3=3
4x=12
x=3 4(3)=12
3(3)-2y=3 12=12
9-2y=3
-2y=3-9
-2y=-6
y=3
x=12/4 tirar prova a limpo: 3x -2y=3 3(3)-2(3)=3
9-6=3
3=3
4x=12
x=3 4(3)=12
3(3)-2y=3 12=12
9-2y=3
-2y=3-9
-2y=-6
y=3
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás